2021
DOI: 10.1186/s12874-021-01404-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on publication dynamics and non-COVID-19 research production

Abstract: Background The COVID-19 pandemic has severely affected health systems and medical research worldwide but its impact on the global publication dynamics and non-COVID-19 research has not been measured. We hypothesized that the COVID-19 pandemic may have impacted the scientific production of non-COVID-19 research. Methods We conducted a comprehensive meta-research on studies (original articles, research letters and case reports) published between 01/0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 33 publications
(32 reference statements)
2
58
0
5
Order By: Relevance
“…The COVID-19 pandemic has mobilized scientists around the world and has resulted in an increase in the number and rate of peer-reviewed articles published, whilst subsequently decreasing the number of non-COVID-19-related articles published in leading health science journals [19]. This phenomenon of an exponential increase in COVID-19 publications may be linked to several reasons: (a).…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has mobilized scientists around the world and has resulted in an increase in the number and rate of peer-reviewed articles published, whilst subsequently decreasing the number of non-COVID-19-related articles published in leading health science journals [19]. This phenomenon of an exponential increase in COVID-19 publications may be linked to several reasons: (a).…”
Section: Discussionmentioning
confidence: 99%
“…Since late 2019, a newly emerging disease, coronavirus disease 2019 (COVID-19), has affected several aspects of health, including physical activity [ 5 , 6 , 7 , 8 , 9 ]. A study by Raynaud et al showed a rise in COVID-19 related publications and a decrease in the proportion of non-COVID-19 publications in high-impact medical journals [ 10 ]. Riccaboni and Verginer analyzed the impacts of COVID-19 on research in the PubMed database and found the COVID-19 pandemic induced a sudden surge in COVID-19 related publications [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a comprehensive meta-research on original articles, research letters and case reports published between January 01, 2019 and January 01, 2021 in 10 high-impact medical and infectious disease journals (New England Journal of Medicine, Lancet, Journal of the American Medical Association, Nature Medicine, British Medical Journal, Annals of Internal Medicine, Lancet Global Health, Lancet Public Health, Lancet Infectious Disease and Clinical Infectious Disease), the authors found a dramatic rise in COVID-19 publications accompanied by a substantial decrease (18%) of non-COVID-19 research [ 47 ]. Overall, 1022/6319 (16.2%) were related to COVID-19 research, that was responsible for lower percentage of original articles (47.9% vs .…”
Section: Introductionmentioning
confidence: 99%
“…Overall, 1022/6319 (16.2%) were related to COVID-19 research, that was responsible for lower percentage of original articles (47.9% vs . 71.3%) [ 47 ].…”
Section: Introductionmentioning
confidence: 99%